PENGEMBANGAN MATERI AJAR TEKS LAPORAN HASIL OBSERVASI BERMUATAN KEARIFAN LOKAL PADA SISWA SMP KELAS VIII - Tarigan, Novia; Atika Wasilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study developed instructional materials for observation report texts (LHO) incorporating local wisdom for eighth-grade students at SMP Negeri 1 Dolok Silau. Using the 4D (Define, Design, Develop, Disseminate) research and development (R&D) model, this study focused on needs analysis, material design, and product development. The analysis results indicate that students struggle to understand and compose LHO, and existing teaching materials lack contextual relevance and have not integrated local wisdom. Teachers also require teaching materials relevant to students’ lives. The developed product consists of printed teaching materials with content and visuals that integrate local wisdom, such as the marharoan bolon tradition and annual work cycles from North Sumatra. This material was rated “very good” by subject matter experts (95% and 94%) and teachers (90%), indicating its suitability for use in instruction. This development contributes to improving students’ understanding and skills in writing LHO, while fostering character and a love for local culture.